Хірургічне лікування пацієнтів із переломами кісточок гомілки та ушкодженням синдесмозу - Кожем'яка, Максим Олександрович; Головаха, Максим Леонідович; Kozhemyaka, M. O.; Golovaha, M. L. (Ин-т патологии позвоночника и суставов им. проф. М. И. Ситенко НАМН Украины, 2018)
Ушкодження надп’ятково-гомілкового суглоба (НГС) займають одне з перших місць у структурі травм нижніх кінцівок опорно-рухової системи за- галом, де становлять від 10 до 20 %. При цьому закриті переломи кісточок складають від 30 до 45 % усіх переломів гомілки [1, 2]. Однією з головних проблем у разі травми зазначеної ділянки скелета є лікування нестабільних переломів кісточок із ушкодженням міжгомілкового синдесмозу (МГС), які становлять від 12 до 37 % серед усіх травм НГС [1]. Сьогодні більшість ортопедів у лікуванні пацієнтів із нестабільними переломами кісточок віддають перевагу хірургічним методам. При цьому найбільш дискутабельним залишаєть ся питання щодо способу стабілізації МГС [3–5]. Мета роботи: оцінити результати хірургічного лікування пацієнтів із переломами кісточок з ушкодженням міжгомілкового синдесмозу шляхом аналізу показників функціонального стану надп’ятково-гомілкового суглоба й оцінювання якості життя в післяопераційному періоді. Treatment of unstable ankle joint fractures with damage of syndesmosis is one of important problems in modern traumatology practice. Objective: to evaluate the results of surgical treatment of patients with ankle joint fractures and damage of syndesmosis due to analysis of functional ankle state and assessment of life quality in postoperative period. Methods: we analyzed the results of surgeries of 80 patients (18–67 y. o.) with ankle joint fracture and damage of syndesmosis. In all cases we made osteosynthesis and restoring of syndesmosis stability with following course of rehabilitation, which was the same in our groups. In the main group 44 patients we used developed devices (modeling plates with polyaxial screws blocking for external malleous and tight loops for syndesmosis stabilization). In comparative group (36 patients) we used method АО/ASIF (for external malleous we used AO ⅓ and 1–2 cortical screws of 3.5 mm for syndesmosis fixation). We assessed the results of treatment in 3, 6, 12 months after surgery with 100 score Ankle-Hindfoot Scale AOFAS and SF-36 system. Results: it was established that in the early terms after surgery (3 mon.) in the main group the functional results were better according to AOFAS scale on 17 %. The quality of life according to SF-36 was also better: the signs of physical condition — 21 %, psychological — 7,4 %. Conclusions: suggested method combines stable osteosynthesis of external malleous fractures with stable dynamic fixation of syndesmosis, it allow in improve the life quality and to get excellent and good results in 95.5 % cases. Лечение нестабильных переломов лодыжек с повреждением межберцового синдесмоза (МБС) является важной проблемой современной травматологии. Цель: оценить результаты хирургического лечения пациентов с переломами лодыжек и повреждением МБС путем анализа показателей функционального состояния голеностопного сустава и оценки качества жизни в послеоперационном периоде. Результаты: установлено, что в ранние сроки после операции (3 мес.) в группе исследования функциональные результаты по шкале AOFAS были лучшими на 17 %. Качество жизни по системе SF-36 в группе исследования также было существенно лучше: по показателю физического компонента здоровья — на 21 %, психологического — на 7,4 %. Выводы: предложенная методика сочетает стабильный остеосинтез переломов латеральной лодыжки со стабильной динамической фиксацией МБС, что позволяет повысить качество жизни пациентов, а также получить отличные и хорошие результаты лечения в 95,5 % случаев.
Surgical treatment of patients with ankle joint fracture and damage of syndesmosis
Keywords: переломи кісточок; міжгомілковий синдесмоз; напружені петлі; хірургічна травматологія; ankle fractures; syndesmosis; tight loops; surgical traumatology; переломы лодыжек; межберцовый синдесмоз; напряженные петли; хирургическая травматология